2018
DOI: 10.17221/114/2017-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal B-lymphoblastic lymphoma in a dog: a case report

Abstract: ABSTRACT:A four-year-old Bullmastiff weighing 44 kg was presented with a 14-day history of weight loss, vomiting and diarrhoea. Abdominal ultrasonography showed the presence of abdominal lymphadenopathy and thickening of the wall of the descending colon. Esophagogastroduodenoscopy and colonoscopy with biopsy were performed. Histological examination revealed a high-grade lymphoblastic lymphoma, flow cytometric analysis detected malignant cells of the immature B phenotype. PCR for antigen receptor rearrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Moreover, there have been a small number of cases of B‐cell GIL with long‐term survival. 15 , 16 Furthermore, colorectal lymphomas in dogs often originate in B‐cells and survive long term. 17 , 18 A case report found that a miniature dachshunds (MD) dog had a good prognosis and different characteristics than usual and occur at a younger age (mean age = 4 years).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there have been a small number of cases of B‐cell GIL with long‐term survival. 15 , 16 Furthermore, colorectal lymphomas in dogs often originate in B‐cells and survive long term. 17 , 18 A case report found that a miniature dachshunds (MD) dog had a good prognosis and different characteristics than usual and occur at a younger age (mean age = 4 years).…”
Section: Introductionmentioning
confidence: 99%
“…T‐cell lymphoma account for 63% to 91% of GIL in dogs 6‐8,13,14 ; the higher proportion of T‐cell lymphoma might be 1 factor associated with shorter MST. Moreover, there have been a small number of cases of B‐cell GIL with long‐term survival 15,16 . Furthermore, colorectal lymphomas in dogs often originate in B‐cells and survive long term 17,18 .…”
Section: Introductionmentioning
confidence: 99%